2017
DOI: 10.1016/j.neubiorev.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

The brain map of gait variability in aging, cognitive impairment and dementia—A systematic review

Abstract: While gait variability may reflect subtle changes due to aging or cognitive impairment (CI), associated brain characteristics remain unclear. We summarize structural and functional neuroimaging findings associated with gait variability in older adults with and without CI and dementia. We identified 17 eligible studies; all were cross-sectional; few examined multiple brain areas. In older adults, temporal gait variability was associated with structural differences in medial areas important for lower limb coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 60 publications
7
116
0
1
Order By: Relevance
“…For example, subclinical brain vascular abnormalities, measured on brain MRIs as infarcts and white matter hyperintensities, were reported to associate with greater variability of spatial gait parameters (step length) (Rosano et al 2007). In older adults, gait variability is thought to be associated with areas important for sensorimotor integration, coordination (Tian et al 2017), and memory and executive function (Rosso et al 2014). In the present study, there was a discernible trend for increased gait variability after induction of neurovascular uncoupling.…”
Section: Discussionsupporting
confidence: 51%
“…For example, subclinical brain vascular abnormalities, measured on brain MRIs as infarcts and white matter hyperintensities, were reported to associate with greater variability of spatial gait parameters (step length) (Rosano et al 2007). In older adults, gait variability is thought to be associated with areas important for sensorimotor integration, coordination (Tian et al 2017), and memory and executive function (Rosso et al 2014). In the present study, there was a discernible trend for increased gait variability after induction of neurovascular uncoupling.…”
Section: Discussionsupporting
confidence: 51%
“…(Cremers et al, 2012) In addition, decreased ACC integrity has been associated with increased gait variability among older adults. (Tian et al, 2017) Further, electroencephalographic recording over the SFG/ACC region during treadmill gait in healthy young adults has shown that this region is rhythmically active in synchrony with the gait cycle. (Gwin et al, 2011, Knaepen et al, 2015) This activity is the most pronounced during trailing limb push off and leading limb initial contact, similar to the gait-related activation pattern of the sensorimotor cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have attempted to elucidate the neural correlates of these age‐related deviations from normal gait . For instance, gait variability has been associated with several volumetric neuroimaging markers, including larger temporal horns, smaller middle portion of ventricular bodies, reduced total brain volume, lower hippocampus and anterior cortex volume, and lower microstructural integrity in normal‐appearing white matter and in white matter lesions . Additionally, white matter hyperintensities, brain infarcts, and brain atrophy have also been found to predict increases in step length variability and decreases in gait speed and stride length .…”
Section: The Act Of Walking In Normal Agingmentioning
confidence: 99%
“…Evidence shows an overlap between areas responsible for multisensory and higher order cognitive processing (e.g., executive functions) and those involved in sensorimotor integration and motor control (Fig. ) . Specifically, frontal and parietal areas (e.g., PFC, primary motor cortex, and superior parietal cortex) are involved in multisensory processing, executive functions, and complex motor behavior .…”
Section: Exploiting the Benefits Of Multisensory Processing For Succementioning
confidence: 99%